CARDIOVASCULAR DISEASES ASSOCIATED WITH PSEUDOEXFOLIATION SYNDROME – A PROSPECTIVE CROSS-SECTIONAL STUDY - CHELLAKUMAR, VIKRAM; RASHMI PRIYANKA; BALAKRISHNAN M (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objectives: In recent years, pseudoexfoliation syndrome (PXF) is recognized as a systemic disorder and as an independent risk factor for cardiovascular diseases including hypertension, angina, myocardial infarction, and stroke. We studied the prevalence of cardiovascular diseases associated in patients with PXF. Methods: It was a prospective cross-sectional study done over a period of 2 years from January 2017 to December 2018 at the Department of Ophthalmology in Sree Balaji Medical College and Hospital. A total of 100 patients with PXF both male and female above the age of 50 were included in the study. They were given a standard questionnaire to evaluate common cyclic vomiting syndrome symptoms and a history of angina, myocardial infarction, and cerebrovascular accident was noted. All patients underwent blood pressure (BP) measurement and electrocardiogram (ECG) recording. Results: In our study which included 100 patients with PXF there were 57 male patients and 43 female patients. Most of the patients (59%) were above 65 years of age and 36 patients were diagnosed with open-angle glaucoma. A total of 62 patients had persistently elevated BP on three different occasions. Only five patients gave a positive history of angina at some point in their lives and among them, only four patients showed demonstrable changes in ECG. One patient gave a history of myocardial infarction (two showed changes in ECG) and none of the patients had cerebrovascular accidents. Conclusion: Our study showed that more than 60% of patients with PXF had hypertension; however, a statistically significant association with other conditions was not noted.